2014
DOI: 10.1002/2014jd021507
|View full text |Cite
|
Sign up to set email alerts
|

Correcting the record of volcanic stratospheric aerosol impact: Nabro and Sarychev Peak

Abstract: Since 2010, several papers have been published that reveal a pattern of discrepancies between stratospheric aerosol data from the Optical Spectrograph and Infrared Imaging System (OSIRIS) instrument and other measurements and model simulations of volcanic plumes from Kasatochi, Sarychev Peak, and Nabro volcanoes. OSIRIS measurements show two discrepancies, a posteruption lag in aerosol onset/increase and a low bias in maximum stratospheric aerosol optical depth. Assumed robustness of the OSIRIS data drove vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 67 publications
1
76
0
Order By: Relevance
“…Numerous previous studies have documented this eruption, with many of them focusing on whether Nabro injected SO 2 directly into the stratosphere or whether the injection was associated with monsoon circulation (Bourassa et al, 2012(Bourassa et al, , 2013Sawamura et al, 2012;Vernier et al, 2013;Fromm et al, 2013Fromm et al, , 2014Clarisse et al, 2014;Biondi et al, 2016).…”
Section: Africa: Dalafilla Nabromentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous previous studies have documented this eruption, with many of them focusing on whether Nabro injected SO 2 directly into the stratosphere or whether the injection was associated with monsoon circulation (Bourassa et al, 2012(Bourassa et al, , 2013Sawamura et al, 2012;Vernier et al, 2013;Fromm et al, 2013Fromm et al, , 2014Clarisse et al, 2014;Biondi et al, 2016).…”
Section: Africa: Dalafilla Nabromentioning
confidence: 99%
“…A more detailed study of the Nabro eruption, also using the C12 IASI retrieval scheme, is reported in Fromm et al (2014), and concluded that "Nabro injected sulphur directly to or above the tropopause upon the initial eruption on 12/13 June, and again on 16 June 2011". Here we include the Nabro summary of the C12 IASI data set.…”
Section: Africa: Dalafilla Nabromentioning
confidence: 99%
“…The identification and the relative importance of different transport pathways of tropospheric source gases found within the Asian monsoon anticyclone into the lower stratosphere are the subject of a longstanding debate (Dethof et al, 1999;Park et al, 2004;Randel et al, 2010;Bian et al, 2012;Bourassa et al, 2012;Ploeger et al, 2013;Fairlie et al, 2014;Fromm et al, 2014;Uma et al, 2014;Vogel et al, 2014Vogel et al, , 2015Garny and Randel, 2016;Tissier and Legras, 2016;Orbe et al, 2015). The influence of these different transport pathways on the chemical composition of the extratropical upper troposphere and lower stratosphere (ExUTLS) is important because changes in ozone and water vapor in the ExUTLS have a significant impact on surface climate, even if the perturbation is relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…The value of SOD is held constant at 0.0035 for October 2012 onwards, due to unavailability of data from the Sato et al (1993) for more recent periods of time. The Sato et al (1993) SOD record resolves the recent eruptions of Kasatochi, Sarychev and Nabro (Rieger et al 2015;Fromm et al 2014), but stops short of the April 2015 eruption of Calbuco that deposited sulfate into the high latitude, summer stratosphere (Solomon et al 2016). Since the perturbation to global SOD due to volcanic eruptions between the end of 2012 and summer 2016 is small, the use of a constant value for SOD since October 2012 has no bearing on any of our scientific conclusions.…”
Section: Model Inputsmentioning
confidence: 78%